Computed Tomographic Exploration of the Middle Ethmoidal Artery - Mason, Eric; Solares, C. Arturo; Carrau, Ricardo L.; Figueroa, Ramon (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives The integral involvement of sinus and skull base surgeries in the field of otolaryngology makes the endonasal vasculature including the ethmoidal arteries important to consider. The anterior ethmoidal artery (AEA) and posterior ethmoidal artery (PEA) are well-known entities, yet the relatively recent notion of accessory or middle ethmoidal vessels complicates our understanding of this arterial system.Study Design Radiographic study.Methods Fifty computed tomographic angiographies were studied for the presence of accessory/middle ethmoidal arteries (MEAs). If contrasted arteries were not visualized reliably, foramina were accepted as evidence of arteries. The accessory arteries/foramina were then compared with the locations of the AEA and PEA.Results A total of 19 of the 50 patient samples studied had evidence of a right, left, or bilateral middle ethmoidal vessels (38%). Overall, 26 arteries total were identified out of the 100 sides (26%). Unilateral middle arteries were more common than bilateral, and right sided were more common than left. There was no evidence of multiple MEAs on a given side.Conclusion The endonasal surgeon must be cognizant of the possible presence of MEAs. These arteries should be considered when working in the medial orbit and anterior skull base region.
Keywords: middle ethmoidal artery; ethmoid; accessory; endoscopic skull base surgery; endoscopy; radiology; skull base; anterior skull base; endoscopic sinus surgery